An algorithm to discover any change with the messages or documents which is sent with the internet. - H. Kassim, Najat (University of Thi-Qar Journal of Science, 2011)
This research introduce new algorithm to discover any change in the sender message. Thisalgorithm is programmed with visual Basic language. This algorithm is building frominputing message by the sender to find key or (password) for encoding the senderinformation , which is append to the original message and will be represents the messagedigital signature. the algorithm of key will be search to find symbols that represents middle of any word,this symbols will be concatenation to produced key in Ascii codes , which sum to producedkey number that is added to each Ascii code from the sender information, as result ,everysymbol is converted to Ascii code to produced new code append with message. the receiverwill be produced key with the same algorithm above, then using it to decode messagesignature , by using the reverse algorithm of encoding , if this document or message is right,so the user information is read to know him .otherwise, the receiver will not decode thisinformation so ,may be this document or message changed.